2012
DOI: 10.1111/bjd.12024
|View full text |Cite
|
Sign up to set email alerts
|

Primary upper-limb lymphoedema

Abstract: Primary ULL appears later in life than LLL, without predominance in either sex. Infectious complications are rare and patients considered the lymphoedema volume stable throughout life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…The interpretation criteria for evaluating lymphatic dysfunction included inguinal lymph node–uptake asymmetry, compared with the contralateral side, ranging from the total absence of visualization to intermediate, diminished lymph node uptake or a normal appearance. Popliteal node visualization was considered an important sign of abnormal lymphatic function, as it suggests rerouting through the deep lymphatic system …”
Section: Primary Lymphoedema Topography In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…The interpretation criteria for evaluating lymphatic dysfunction included inguinal lymph node–uptake asymmetry, compared with the contralateral side, ranging from the total absence of visualization to intermediate, diminished lymph node uptake or a normal appearance. Popliteal node visualization was considered an important sign of abnormal lymphatic function, as it suggests rerouting through the deep lymphatic system …”
Section: Primary Lymphoedema Topography In Childrenmentioning
confidence: 99%
“…Popliteal node visualization was considered an important sign of abnormal lymphatic function, as it suggests rerouting through the deep lymphatic system. 8,9 Lower-limb lymphoscintigraphy was abnormal (diminished/absent groin lymph node uptake, dermal back flow) in 56 of the 64 (88%) patients tested (Fig. 1d).…”
mentioning
confidence: 98%
“…17 Ovarian carcinoma and uterine carcinoma were the most common malignancies. 10,17 Vignes et al, 18 in a review of 60 patients with primary upper limb lymphedema, found similar incidence in males and females, with a mean age at onset of 38.5 years (range 3-82 years). The hand was affected in all patients, the forearm in 55%, and the upper arm in 23%.…”
Section: Discussionmentioning
confidence: 88%
“…The hand was affected in all patients, the forearm in 55%, and the upper arm in 23%. 18 Twenty-one patients (35%) had associated lower limb lymphedema. Patients were followed for a median period of 103 months, and lymphedema was stable in 95%.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoedema is a particular type of oedema caused by a congenital or acquired deficiency of the lymphatic system, resulting in an accumulation of protein‐rich fluid in the dermis and hypodermis . Primary lymphoedemas are a heterogeneous group of genetic diseases with known mutations of the VEGFR3 gene in the case of Milroy's disease and of the FOXC2 gene in lymphoedema associated with distichiasis , resulting in functional abnormality of the lymphatic system.…”
mentioning
confidence: 99%